Malaria and associated factors among under-five children in Borena pastoral communities, southern Ethiopia - Aliyo, Alqeer; Golicha, Wako; Fikrie, Anteneh (Frontiers in Parasitology, 2024)
Background Malaria continues to be an important threat to public health and infects millions of children under 5 years of age each year. Although Ethiopia has set targets for at-risk group interventions to eradicate and manage malaria, the illness is still a serious public health problem in areas where it is endemic, especially in the unique lowlands in the Borena zone. Objective This study aimed to determine the prevalence of malaria and associated factors among children in Borena’s pastoral communities, Oromia Regional State, southern Ethiopia, in 2022. Methods A community-based cross-sectional study was conducted from 1 March to 30 April 2022 among 437 randomly selected households with children under 5 years of age in pastoral communities in the Borena zone. Data were collected through face-to-face interviews with structured and pretested questionnaires and blood sample examination using microscopy. Thick and thin blood smears were prepared and examined under a microscope at a health center to confirm malaria cases. The data were analyzed using SPSS version 25. Bivariate and multivariable logistic regression analyses were used to identify factors associated with malaria, and a p-value <0.05 was used to declare statistical significance. Result The prevalence of malaria among children under 5 years of age was 27.8% (95% CI = 23.5–32.1), and the prevalence rates of Plasmodium falciparum, Plasmodium vivax, and mixed malaria were 68.4%, 25.6%, and 6%, respectively. Regarding the proportion of malaria among age groups, 81% of children under 5 years of age between 48 and 59 months were malaria-positive. In this study, fever within the last week (AOR = 13.34, 95% CI = 6.37–27.95) and not sleeping under insecticide-treated nets (ITNs) (AOR = 3.10, 95% CI =1.95–4.92) were significantly associated with malaria. The age of the children was negatively associated with malaria prevalence. Conclusion The prevalence of malaria among children under 5 years old was high during the rainy season in this pastoral region of Ethiopia. Factors such as fever within the last week and not sleeping in insecticide-treated nets were significantly associated with malaria. Therefore, to reduce malaria-related infections and deaths among children under 5 years of age, the government ought to enhance the availability and utilization of insecticide-treated nets (ITNs).